Gambaran Tingkat Kemandirian Pasien Pasca Stroke di RSUD Tabanan - Surya Artajaya, Kadek Dwi; Dewi, Ni Luh Putu Thrisna; Pramesti, Theresia Anita (Pustaka Galeri Mandiri, 2025)
Stroke is one of the leading causes of disability that results in decreased patients’ ability to perform daily activities. Physical impairments such as hemiparesis, reduced mobility, and changes in cognitive function contribute to the low level of independence among post-stroke patients. This study aimed to describe the level of independence of post-stroke patients at the Neurology Outpatient Clinic of RSUD Tabanan. This research was a quantitative study with a descriptive design, involving 68 respondents selected through purposive sampling. The instrument used was the Barthel Index to assess the level of independence in activities of daily living (ADL). Data analysis was conducted using univariate descriptive analysis. The results showed that the majority of post-stroke patients were in the category of mild dependence, with 24 respondents (35.3%), followed by moderate dependence in 17 respondents (25%), full independence in 15 respondents (22.1%), total dependence in 7 respondents (10.3%), and severe dependence in 5 respondents (7.4%). The predominance of dependency among post-stroke patients may be attributed to motor impairments, limited mobility, and suboptimal recovery processes. However, factors such as duration since stroke onset, severity of the condition, consistency of rehabilitation, family support, and access to rehabilitation services may play an important role in improving patients’ ability to perform daily activities independently